Pengaruh Kecerdasan Emosional, Kecerdasan Intelektual Dan Kecerdasan Spiritual Terhadap Peningkatan Kinerja Pegawai - Bangkit Tua Wardana Ritonga; Hendra Gunawan Sihombing; Imam Sudirman; Hazrulta Aulia; Taufik Umri; Safrida Safrida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to find out the influence jointly or partially between Emotional Intellegence, Intellectual Intellegence and Spritual Intellegence to the performance of the Workers at the Badan Pengelolaan Pajak dan Retribusi Daerah Provinsi Sumatera Utara UPT Aek Kanopan. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Fourty six workers become the sample of this research. Data analysis technique used is linear regression which shows that from the three independent variables applied to the regression model (Emotional Intellegence, Intellectual Intellegence and Spritual Intellegence). Emotional Intellegence is significant for 0,000 which can be concluded that Emotional Intellegence affects performance (hypothesis 1 accepted). Competantion has significant value 0,026 which can be concluded that competation affects performance (hypothesis 2 accepted). Spritual Intellegence variable has significant value 0,043 which means that Spritual Intellegence influences performance (hypothesis 3 accepted). Research results show that Emotional Intellegence, Intellectual Intellegence and Spritual Intellegence all positively influence the performance of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than α (α=0,05). So, it can be said that Emotional Intellegence, Intellectual Intellegence and Spritual Intellegence influence positively the performance of the workers. Thus, hypothesis 4 accepted.